Получение высокочистых гранулированных металлов: кадмия, цинка, свинца - Щербань, А.П.; Ковтун, Г.П.; Горбенко, Ю.В.; Солопихин, Д.А.; Вирич, В.Д.; Пироженко, Л.А. (Технология и конструирование в электронной аппаратуре, 2017)
Предложены комплексные процессы глубокого рафинирования кадмия, цинка и свинца дистилляцией в вакууме. Разработано устройство для получения гранул. Исследован процесс гранулирования высокочистых металлов. Чистота получаемых гранул кадмия и цинка выше 99,9999, а гранул свинца — выше 99,9995 мас. %. Запропоновано комплексні процеси глибокого рафінування кадмію, цинку і свинцю дистиляцією у вакуумі. Розроблено пристрій для одержання гранул. Досліджено процес гранулювання металів високої чистоти. Чистота одержуваних гранул кадмію і цинку більша за 99,9999, а гранул свинцю — більша за 99,9995 мас. %. Для запобігання окисленню гранул металів при зберіганні на повітрі проведені дослідження процесів пасивації їх поверхні хімічним методом. Підвищенню стійкості до атмосферної корозії гранул сприяє застосування органічних розчинників на основі диметлформаміду як охолодної рідини у процесі гранулювання Cd, Zn і Pb високої чистоти. Cadmium, zinc and lead are constituent components of many semiconductor compounds. The obtained high purity distillates and ingots are large-size elements, which is not always convenient to use, and thus require additional grinding, which does not always allow maintaining the purity of the original materials. For the growth of semiconductor and scintillation single crystals it is advisable to use «friable» granular high-purity distillates, which can be processed without the risk of contamination. For example, the European low-background experiment LUCIFER required more than 20 kg of high-purity granulated zinc, which was agreed to be supplied by NSC KIPT. This task was then extended to cadmium and lead. Motivated by these tasks, the authors of this paper propose complex processes of deep refining of cadmium, zinc and lead by vacuum distillation. A device producing granules has been developed. The process of granulation of high-purity metals is explored. The purity of produced granules for cadmium and zinc is >99,9999, and >99,9995% for lead granules. To prevent oxidation of metal granules during exposition to air, chemical methods of surface passivation were used. Organic solvent based on dimethylformamide used as a coolant improves the resistance of granules to atmospheric corrosion during the granulation of high purity Cd, Zn and Pb.